The effect of biostatistics course among undergraduate nursing students - Khaskheli, Munwar- us- Salam; Rehana Khatoon; Rubina Parveen; Saad Raza; Muhammad Rahimon; Benazeer Maria (Medical Journal of South Punjab, 2024)
Objective: To highlight the Effect of Biostatistics Course Among Undergraduate Nursing Students Methodology: A Quasi Expermenatl study design was used. Study conducted at nursing institute of Peoples University of Medical & Health Sciences, Nawabshah & Affiliated colleges. All bachelors’ Science nursing students (Generic) 3rd year 6th semester students were study subjects. Sample size was 150 student nurses. The questionnaire was developed and modified after literature searched . Data collected and analyzed through the SPSS version 25 software (Statistical Packages for Social Sciences). Results: The mean age of the participants was 22 years, with a standard deviation of ± 1.517. Of them, 57.33% were female and 42.67% were male. “In which year should biostatistics education be taught in nursing school”, responses were assessed; the findings showed that, in the pre-evaluation, the majority of responses (76%) and in the post-evaluation, the majority of responses (88%). the impact of pre- and post-training biostatistics as well as nursing students’ perspectives on the field. When asked if they had previously received lessons in biostatistics (or statistics), studying students responded with YES in 47 (31.2%) and NO in 103 (688.8%) of the questions that were assessed. A significant difference was observed between the pre and post-effect (p <0.001). Conclusion: it is concluded that the Effect of Biostatistics Course Among Undergraduate Nursing Students was highly significant with their pre and post training course.